(1571) Expert systems-An overview الأنظمة الخبيرة - نظرة عامة - El Daoushy, Abdalla (The Institute of National Planning, 2018)
At present, the most important application areas of Artificial Intelligence (AI) would be centered on knowledge engineering. and ,more particularly, on Expert Systems (ESs). Today, ESs are used in business, science, engineering, manufacturing, and many other fields.